Multiple keratoacanthoma Involving Lower Lip: Case Report and literature review - Hamouda , Saleh A.; Elmurtadi, Ali M.; EL Warfalli, Howida; Hamouda, Nairouz (Libyan Journal of Dentistry, 2023)
Keratoacanthoma (KA) is a benign epithelial proliferative lesion which frequently occurs on the sun exposed areas of the skin. KA originates within the pilosebaceous apparatus of the skin, may be solitary or multiple and character by spontaneous resolution. Keratoacanthoma is believed to have a good prognosis despite its clinical and histological resemblance to well differentiated squamous cell carcinoma (SCC). The aim of this paper is to briefly review and discuss the literature about multiple keratoacanthoma involving the lower lip in a 67-year-old male.